PENGARUH METODE PEMBELAJARAN DAN PENUGASAN TERHADAP EFEKTIVITAS PEMBELAJARAN EKONOMI DI SMA NEGERI 2 RAMBATAN - Fitriany Febby Adiana; Mawardi Effendi (Program Magister Pendidikan Ekonomi (S2), 2014)
This research is empirically aimed to analyze and explain the data about the effectiveness learning using assignment learning methods on economy subject in SMAN 2 Rambatan. The popullation on the research were student of SMAN 2 Rambatan consist of 9 classes, totally 206 students. The sampling quantity is 40 persons. The technique sample is cluster sampling through random vote. The research data was collected by observation sheet, testing, and questionaries. Design used in research is Block Design. There are 2 free variables; firstly, learning methods (A) consist of 2 categories, Snowball Throwing Methods (A1) and Cooperative STAD Methods (A2); secondly, assignment (B) consist of 2 categories, they were wihtout giving pre-assignment (B1) and giving pre-assignment (B2). In This research is effective learning with related variabels learning activity indicators, cognitive level, learning creativity, accuracy learning out put, and students responses. Data analysis used in this research are (1) descriptive analysis, (2) requirement testing analysis, and (3 analysis of varianc. The research show that (1) hypotesis testing result for learning methods state Ftest ≥ Ftab0,05 (27,84 ≥ 10,51), means that there is significant different, learning effectiveness from class which use snowball throwing methods with cooperative STAD learning methods. As effective learning to cooperative STAD learning 43,85% meanwhile snowball thowing 40,87%. (2) Hypotesis test result for assignment show Ftest ≥ Ftab0,05 (727,84 ≥ 10,51), means there is significant different learning effectiveness from the class whiout giving pre-assignment with giving pre-assignment. Whereas, the effective leraning from the class which is given pre-assignment is higher (48,98%) meanwhile the class which is not given pre-assigment only 34.73%. Key Words: learning efektiveness, learning methods, assignment consist, pre-assignment